2009
DOI: 10.1088/0963-0252/18/3/035012
|View full text |Cite
|
Sign up to set email alerts
|

Langmuir probes in RF plasma: surprising validity of OML theory

Abstract: Low-temperature, partially ionized plasmas are commonly used in industry for materials processing, and many of these are created by radiofrequency (RF) power. For the characterization of plasma sources, electrostatic probes are the easiest to use, but interpretation of the current-voltage (I -V) curves is not straightforward. The presence of strong RF pickup and neutral collisions further complicates the problem. Langmuir's orbital-motionlimited (OML) theory provides a simple formula for ion current, but this … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
66
0
1

Year Published

2011
2011
2020
2020

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 97 publications
(70 citation statements)
references
References 24 publications
2
66
0
1
Order By: Relevance
“…The vertical plasma symmetry can be thus quantified by comparison of the positive ion densities measured at the edge positions, whereas at the centered position of the top probe relevant plasma parameters for comparison with the source performance are determined. The positive ion density is evaluated using a fit of the OML ion current on the positive ion part of the measured characteristic [13]. Of particular interest is the sheath potential profile in front of the extraction apertures, which is calculated as the difference between the potential of the plasma grid (= bias potential) and the plasma potential, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…The vertical plasma symmetry can be thus quantified by comparison of the positive ion densities measured at the edge positions, whereas at the centered position of the top probe relevant plasma parameters for comparison with the source performance are determined. The positive ion density is evaluated using a fit of the OML ion current on the positive ion part of the measured characteristic [13]. Of particular interest is the sheath potential profile in front of the extraction apertures, which is calculated as the difference between the potential of the plasma grid (= bias potential) and the plasma potential, i.e.…”
Section: Methodsmentioning
confidence: 99%
“…It was determined from the electron current at the plasma potential, from the integral of the EEDF using Druyvesteyn formula and from the square of the electron current in the electron saturated region according to so called orbital motion limit model [19][20][21]. It was determined from the electron current at the plasma potential, from the integral of the EEDF using Druyvesteyn formula and from the square of the electron current in the electron saturated region according to so called orbital motion limit model [19][20][21].…”
Section: Langmuir Probe Diagnosticsmentioning
confidence: 99%
“…In fact, Piel et al 8 and Barjatya et al 4 have shown that that although the general expression remains the same, the β factor varies even for a specific probe geometry. At the same time, recent work by Bekkeng et al 15 and Chen 16 has shown that the approximated expressions are indeed valid, both in space and in laboratory plasma, as long as the probe design adheres to keeping the dimensions smaller than any Debye length encountered. Thus, we have chosen to use the approximated OML theory current collection expressions in the model, not only because they are easier to implement, but also because effects on the I-V characteristic due to deviation from OML expressions are expected to be smaller than that caused by contamination or by surface to probe area ratio.…”
Section: Spice Model Setupmentioning
confidence: 84%